2018
DOI: 10.1029/2018je005580
|View full text |Cite
|
Sign up to set email alerts
|

The Far Ultraviolet Wavelength Dependence of the Lunar Phase Curve as Seen by LRO LAMP

Abstract: We present detailed photometric properties of the Moon at far ultraviolet wavelengths. The far ultraviolet data from the Lunar Reconnaissance Orbiter (LRO) Lyman Alpha Mapping Project (LAMP) instrument were used to derive two Hapke photometric parameters, the single‐scattering albedo, w, and the asymmetry factor, b, in the single‐particle phase function, for selected mare and highland regions. The derived single‐scattering albedo spectra show blue slopes for both regions. Furthermore, the negative values of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…In that study, wavelength‐dependent asymmetry parameters (g) were derived for highlands and mare terrains using data in the 27–73° phase angle range using a single‐lobed Henyey‐Greenstein phase function. Based on those results, we use g = −0.48 in this analysis, which is well within the error bars of Liu et al () for both highlands and mare regions at all wavelengths considered here. Hendrix et al () showed that the lunar spectral slopes measured in the 164–173 nm region are controlled by level of hydration and are found to be diurnally variable; an adjacent spectral region (175–190 nm) is not affected by hydration and shows no trend with local time, supporting the case that the slopes in the 164–173 nm region—and their variation throughout the lunar day—are indeed due to hydration.…”
Section: Discussionsupporting
confidence: 72%
“…In that study, wavelength‐dependent asymmetry parameters (g) were derived for highlands and mare terrains using data in the 27–73° phase angle range using a single‐lobed Henyey‐Greenstein phase function. Based on those results, we use g = −0.48 in this analysis, which is well within the error bars of Liu et al () for both highlands and mare regions at all wavelengths considered here. Hendrix et al () showed that the lunar spectral slopes measured in the 164–173 nm region are controlled by level of hydration and are found to be diurnally variable; an adjacent spectral region (175–190 nm) is not affected by hydration and shows no trend with local time, supporting the case that the slopes in the 164–173 nm region—and their variation throughout the lunar day—are indeed due to hydration.…”
Section: Discussionsupporting
confidence: 72%
“…This tool enables large spatial coverage and high signal‐to‐noise ratio at low spectral resolution. The second tool we use is the LAMP Spectral Mapper (Byron et al, ; Liu et al, ; Mandt et al, ), which produces 3‐D data cubes over a specified region of interest at up to ~250‐m/pixel spatial resolution. This tool enables higher spectral resolution (68 wavelength bins at 2‐nm resolution) over smaller areas of the lunar surface.…”
Section: Methodsmentioning
confidence: 99%
“…The mapper tools calculate the radiance factor I/F (where I is the radiance measured by LAMP and F is the flux incident upon the surface) by dividing the LAMP‐measured brightness by TIMED SEE solar spectrum data (Woods et al, ), and then correcting for observational geometry using the photometric correction described in Liu et al (). The corrected reflectance product reported in this work is a normalized radiance factor, defined as normalI/Fnorm=normalI/normalFnormalri,e,gris,es,gs where ris,es,gs is the simplified Hapke bidirectional reflectance at the standard angles i = g = 30° and e = 0° (Hapke, ).…”
Section: Methodsmentioning
confidence: 99%
“…The blue slope persists in the single scattering albedo spectra, as w decreases with increasing wavelengths above 130 nm. We find reasonable agreement between the laboratory and LAMP w ( Figure 6, top panel) derived from observations of a sample mare region (Liu et al, 2016(Liu et al, , 2017, despite expected differences in soil porosity/morphology. Apollo soil in the laboratory likely lacks the fairy castle-like structure formed via tribocharging in the low lunar-gravity environment.…”
Section: Journal Of Geophysical Research: Planetsmentioning
confidence: 99%